of social thinking Preparatory stage students (Journal of the College of Basic Education, 2022)
Behavior can be a function of thinking, in the sense that the nature or quality of thinking affects behavior, and that this influence may have a basic role for some individuals in determining the quality of their behavior. (Saleh, 2000, p. 1) However, social thinking, when people pay attention, makes others feel them, and this leads to making others respond to them, which causes social thinking in all circumstances. Visual communication has deeper social meanings, so social thinking about meaning is studied and studied as well